Sistem Informasi Karya Inovatif berbasis CMS Wordpress Studi Kasus STIKI Malang - Adnan Zulkarnain; Arif Tirtana; Decya Windri Sukmawati Susanto (Jurnal Ilmiah Teknologi Informasi Asia, 2020)
Technological developments affect the world of education, especially technology plays a role as a medium for disseminating information through the internet. With the technology, information can be accessed very quickly and easily. Web-based information system is one product of the development of existing technology. Through the data management information system, there are no restrictions on place and time. The development of an Sistem Informasi Karya Inovatif at STIKI Malang is needed to facilitate the management of work data created by students and lecturers. The method used to develop an Sistem Informasi Karya Inovatif is the waterfall method, because this method has a sequential structure so that the development process becomes more controlled. The development of an Sistem Informasi Karya Inovatif STIKI Malang uses an open source application, CMS (Content Management System) Wordpress to accelerate the process of developing information systems. The information system developed utilizes several WordPress plugins such as Advanced Custom Fields and Pods - Custom Content Types and Fields. The information system of student work that has been made is carried out by the testing process using the black box testing method to ensure all information system functions are running well.